Estrogen Signaling Modulates Allergic Inflammation and Contributes to Sex Differences in Asthma - Keselman, Aleksander; Heller, Nicola (Frontiers in Immunology, 2015)
Asthma is a chronic airway inflammatory disease that affects ~300 million people worldwide. It is characterized by airway constriction that leads to wheezing, coughing, and shortness of breath. The most common treatments are corticosteroids and β2-adrenergic receptor antagonists, which target inflammation and airway smooth muscle constriction, respectively. The incidence and severity of asthma is greater in women than in men, and women are more prone to develop corticosteroid-resistant or “hard-to-treat” asthma. Puberty, menstruation, pregnancy, menopause, and oral contraceptives are known to contribute to disease outcome in women, suggesting a role for estrogen and other hormones impacting allergic inflammation. Currently, the mechanisms underlying these sex differences are poorly understood, although the effect of sex hormones, such as estrogen, on allergic inflammation is gaining interest. Asthma presents as a heterogeneous disease. In typical Th2-type allergic asthma, interleukin (IL)-4 and IL-13 predominate, driving IgE production and recruitment of eosinophils into the lungs. Chronic Th2-inflammation in the lung results in structural changes and activation of multiple immune cell types, leading to a deterioration of lung function over time. Most immune cells express estrogen receptors (ERα, ERβ, or the membrane-bound G-protein-coupled ER) to varying degrees and can respond to the hormone. Together these receptors have demonstrated the capacity to regulate a spectrum of immune functions, including adhesion, migration, survival, wound healing, and antibody and cytokine production. This review will cover the current understanding of estrogen signaling in allergic inflammation and discuss how this signaling may contribute to sex differences in asthma and allergy.